Simulation, modeling, and programming for autonomous robots : 4th International Conference, SIMPAR 2014, Bergamo, Italy, October 20-23, 2014. Proceedings - Broenink, Jan F.; Kroeger, Torsten; MacDonald, Bruce A.; Brugali, Davide (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 4th International Conference on Simulation, Modeling, and Programming for Autonomous Robots, SIMPAR 2014, held in Bergamo, Italy, in October 2014. The 49 revised full papers presented were carefully reviewed and selected from 62 submissions. The papers are organized in topical sections on simulation, modeling, programming, architectures, methods and tools, and systems and applications.